Pengaruh Latihan Napas Dalam Dan Dzikir Terhadap Tekanan Darah Pada Lansia Penderita Hipertensi Di Wilayah Kerja Puskesmas Simpang Tiga Pekanbaru - riamah riamah; Maulia Zhafira; Anita Syarifah; M.Irwan (Jurnal Keperawatan Abdurrab, 2026)
Hypertension is one of the diseases of the cardiovascular system that has a high mortality and morbidity rate and is the main killer without symptoms that occurs in the elderly, if not addressed will cause other heart diseases. The purpose of this study was to determine the effect of deep breathing exercise therapy and dhikr on blood pressure in elderly people with hypertension in the work area of Puskesmas Simpang Tiga Pekanbaru. The research design was a quasi-experimental with a pre-post test with a control group. The sampling technique used was non-probability sampling, namely consecutive sampling. The number of respondents was 60 people consisting of 30 respondents in each group. The intervention group was given deep breathing exercise therapy and dhikr while the control group was not. The instrument for systolic and diastolic blood pressure values  used a digital Sphyyangmomamometer. The results of the study using the wicolxon test showed that there was an effect of deep breathing exercise therapy and dhikr on blood pressure in elderly people with hypertension in the work area of  Puskesmas Simpang Tiga Pekanbaru in the intervention group obtained a p value of 0.000 <0.05 while in the control group obtained a p value of 0.046> 0.05. The conclusion is that deep breathing exercises and dhikr therapy for the blood pressure of elderly people with hypertension are effective in lowering blood pressure.